2015
DOI: 10.1371/journal.pone.0127175
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Identifying a Set of microRNAs As Precise Diagnostic Biomarkers of Acute Kidney Injury

Abstract: In the last decade, Acute Kidney Injury (AKI) diagnosis and therapy have not notably improved probably due to delay in the diagnosis, among other issues. Precocity and accuracy should be critical parameters in novel AKI biomarker discovery. microRNAs are key regulators of cell responses to many stimuli and they can be secreted to the extracellular environment. Therefore, they can be detected in body fluids and are emerging as novel disease biomarkers. We aimed to identify and validate serum miRNAs useful for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 38 publications
(42 reference statements)
2
108
1
1
Order By: Relevance
“…miRNAs are already being used commercially as disease biomarkers in oncology [17]. There is evidence for the use miRNAs as biomarkers in a wide range of diseases including prostate cancer [36], cardiac disease [37], acute kidney injury [38], and Alzheimer's disease [39]. If we could identify miRNAs that could be used as biomarkers for PCOS, the diagnosis and treatment of PCOS would be revolutionized.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are already being used commercially as disease biomarkers in oncology [17]. There is evidence for the use miRNAs as biomarkers in a wide range of diseases including prostate cancer [36], cardiac disease [37], acute kidney injury [38], and Alzheimer's disease [39]. If we could identify miRNAs that could be used as biomarkers for PCOS, the diagnosis and treatment of PCOS would be revolutionized.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, urine and plasma miR-21 can predict AKI progression, with an AUC of 0.81 and 0.83, respectively [47]. Moreover, a recent pilot study showed that other sets of microRNAs, including miR-101-3p, miR-127-3p, miR-210-3p, miR-126-3p, miR-26b-5p, miR-29a-3p, miR-146a-5p, miR-27a-3p, miR-93-3p, and miR-10a-5p, were altered several days prior to the increase in SCr, indicating their potential as prognostic AKI biomarkers among ICU patients [48]. Lorenzen et al recently demonstrated that elevated levels of plasma miR-210, a microRNA upregulated by hypoxia-inducible factor, was an independent predictor of mortality, with a hazard ratio (HR) 1.69 in patients with AKI requiring RRT [56].…”
Section: Urine Micrornamentioning
confidence: 97%
“…170 Another study utilized serum samples from normal subjects and patients with AKI; miRNA molecules could be considered as markers of AKI. 171 Notably, several of the miRNA molecules had already been associated with kidney injury: in proximal tubule adhesion and trafficking during IRI (miR-127), in an in vivo mouse model of IRI and in patients with immunoglobulin A nephropathy (miR-146a), and in progression of chronic kidney disease (miR-29a). In addition, several of the miRNA molecules could also be correlated with AKI severity according to the Acute Kidney Injury Network classification.…”
Section: Microrna Molecules As Potential Biomarkers Of Ci-akimentioning
confidence: 99%
“…In addition, several of the miRNA molecules could also be correlated with AKI severity according to the Acute Kidney Injury Network classification. 171 Two groups have found several miRNAs whose serum levels were increased in patients with CI-AKI. 172,173 Future aims could be directed toward identifying miRNAs that are expressed specifically in the kidney 174 and to correlate their changes with kidney injury due to use of CM.…”
Section: Microrna Molecules As Potential Biomarkers Of Ci-akimentioning
confidence: 99%